Collection strategies and delinquency in the Central Western Peru Adventist Educational Association - Romero-Carazas, Rafael (2022)
The social immobilization caused by the COVID-19 pandemic led to the transfer of many students from private to state institutions, due to the fact that their financial managers had difficulties in meeting their current expenses and, additionally, their tuition pension expenses; In this context, the present study justified its elaboration by the need to know the collection strategies and their relationship with delinquency; therefore, the general objective of this research work was to determine to what extent collection strategies and delinquency are related in the Central Western Peru Adventist Educational Association; through a basic study, using a quantitative approach, non-experimental design, cross-sectional and correlational, a questionnaire was applied to a sample of 82 participants, members of the accounting, administrative and teaching staff of the institutions comprising the unit of analysis. After applying the respective statisticians, the results showed a Rho coefficient of (-0.958) and a p value (0.000). It was concluded that there is a strong and inverse relationship between the variables under study; therefore, it is inferred that the greater the presence of collection strategies, the lower the presence of delinquency and vice versa.